Curial e Güelfa y la prosa corta alegórica: los Triunfos de Petrarca en la narrativa en catalán del XV. - RECIO, ROXANA (Scripta, 2013)
The Trionfi of Petrarch enjoyed a wide circulation in Europe, influencing not only in literature. In this article we try to offer a vision of how the work of Italian writer was felt in the Iberian Peninsula and, especially, in the Crown of Aragon. In this sense, it is very remarkable the inspiration from the Trionfo dell'Amore for the anonymous author of Curial, although traces can also be found in other works.